Vigas mistas com laje de concreto e perfis laminados tipo I: análise comparativa do comportamento estrutural entre conectores - RIBEIRO NETO, Juliano Geraldo (2010)
Among the many structural and building systems, it could be highlighted a system that is a mix of steel-concrete that allows the application of their structural and building advantages as whole. When dealing with metal structures, it was noticed some changes regarding the standards of the involved material due to its lack of availability; such measures do not always follow satisfactory structural procedures. This research aims to develop a comparative study about the technical behavior of mixed steel-concrete from three different types of shear connectors (U, U and L cold formed laminated), analyzing their connectors structural behavior when associated with steel beams (Type I rolled and concrete slab). There were three direct shear tests for each type of connector, resulting in a total of nine pieces, and six trials (simply supported composite beams) to evaluate the positive bending moment region. The results indicated that the direct shear behavior between the types of connectors had important and different outcomes; however, they didn t affect significantly the average resistance of the bending mixed beams. Such beams showed considerable results regarding their deflection and deformation performance due to their connectors stiffness.